2021
DOI: 10.3390/molecules26164992
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Dearomative (3+2)-Cycloaddition Involving Nitro-Substituted Benzoheteroarenes under H-Bonding Catalysis

Abstract: In our studies, the organocatalytic 1,3-dipolar cycloaddition between 2-nitrobenzofurans or 2-nitrobenzothiophene and N-2,2,2-trifluoroethyl-substituted isatin imines has been developed. The reaction has been realized by employing bifunctional organocatalysis, with the use of squaramide derivative being crucial for the stereochemical efficiency of the process. The usefulness of the cycloadducts obtained has been confirmed in selected transformations, including aromative and non-aromative removal of the nitro g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“… 61–63 Wang et al reported the first enantioselective dearomative cycloaddition of 2‐nitrobenzofurans and N ‐2,2,2‐trifluoroethylisatin ketimines with dipeptided phosphonium salt catalyst (12 cases, >20:1 dr and 70–94% ee) 61 . During the preparation of this manuscript, Albrecht and coworkers also reported the similar reaction with a cinchona‐derived squaramide as the catalyst (18 cases, >20:1 dr and 77–92% ee) 62 . However, after our extensive and in‐depth research, we successfully discovered that a more readily available chiral cyclohexanediamine‐derived bifunctional tertiary amine‐squaramide catalyst 64–66 could readily catalyze the asymmetric dearomative 1,3‐dipolar cycloaddition reaction of 2‐nitrobenzofurans and N ‐2,2,2‐trifluoroethylisatin ketimines in very high efficiency as well as with excellent diastereoselectivity and enantioselectivity (25 examples, up to 99% yield, >20:1 dr in all cases, and 95–99% ee) under mild reaction conditions (Scheme 1).…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“… 61–63 Wang et al reported the first enantioselective dearomative cycloaddition of 2‐nitrobenzofurans and N ‐2,2,2‐trifluoroethylisatin ketimines with dipeptided phosphonium salt catalyst (12 cases, >20:1 dr and 70–94% ee) 61 . During the preparation of this manuscript, Albrecht and coworkers also reported the similar reaction with a cinchona‐derived squaramide as the catalyst (18 cases, >20:1 dr and 77–92% ee) 62 . However, after our extensive and in‐depth research, we successfully discovered that a more readily available chiral cyclohexanediamine‐derived bifunctional tertiary amine‐squaramide catalyst 64–66 could readily catalyze the asymmetric dearomative 1,3‐dipolar cycloaddition reaction of 2‐nitrobenzofurans and N ‐2,2,2‐trifluoroethylisatin ketimines in very high efficiency as well as with excellent diastereoselectivity and enantioselectivity (25 examples, up to 99% yield, >20:1 dr in all cases, and 95–99% ee) under mild reaction conditions (Scheme 1).…”
Section: Introductionmentioning
confidence: 68%
“…Based on the aforementioned ponder, and inspired by the fact that N-2,2,2-trifluoroethylisatin ketimines play as a type of active and versatile azomehthine ylide precursor for the construction of chiral spirocyclic pyrrolidine-oxindole skeletons via 1,3-dipolar cycloaddition, [53][54][55] as well as in combination with our continuing interest in research on the synthetic methodologies of the CADA reaction of electron-deficient nitroheteroarenes to construct enantioenriched polyheterocycles, [56][57][58][59][60] we envisioned that the dearomative 1,3-dipolar cycloaddition of 2-nitrobenzofurans and N-2,2,2-trifluoroethylisatin ketimines ylide would form spiro-fused pentacyclic compounds with four contiguous stereocenters including two tetrasubstituted stereocenters in a certain catalytic asymmetric fashion, which are characterized by an intriguing fusion of three privileged substructures, the spirocyclic oxindole, pyrrolidine, and hydrobenzofuran motifs (Scheme 1). [61][62][63] Wang et al reported the first enantioselective dearomative cycloaddition of 2-nitrobenzofurans and N-2,2,2-trifluoroethylisatin ketimines with dipeptided phosphonium salt catalyst (12 cases, >20:1 dr and 70-94% ee). 61 During the F I G U R E 1 Selected compounds containing hydrobenzofuran and spirocyclic pyrrolidineoxindole moieties, respectively, and the modular merging strategy for the spiro-fused polyheterocyclic molecular skeletons S C H E M E 1 Readily available chiral cyclohexanediamine-derived bifunctional tertiary aminesquaramide enabling the highly diastereoselective and enantioselective dearomative 1,3-dipolar cycloaddition of 2-nitrobenzofurans and N-2,2,2-trifluoroethylisatin ketimines preparation of this manuscript, Albrecht and coworkers also reported the similar reaction with a cinchonaderived squaramide as the catalyst (18 cases, >20:1 dr and 77-92% ee).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…discovered an asymmetric dearomative [3+2] cycloaddition of 2‐nitrobenzofurans 45 with N ‐2,2,2‐trifluoroethyl‐substituted isatin imines 56 under the catalysis of squaramide‐based bifunctional catalyst C19 , giving the dihydrobenzo‐fused skeletons 64 with a spirooxindole motif in high yields with good diastereo‐ and enantioselectivities (Scheme 25). [42] Alternatively, the 2‐nitrobenzothiophene was well tolerant in this reaction under the catalysis of thiourea catalyst C20 . Almost simultaneously, Wang and co‐workers realized this asymmetric transformation with 2‐nitrobenzofurans or 2‐nitroindoles in the presence of phase‐transfer catalyst C21/C22 , affording the cycloadducts 66 / 67 in satisfactory results [43] .…”
Section: Asymmetric Dearomative Annulations With 2‐nitrobenzofurans A...mentioning
confidence: 99%
“…In 2019, the Yuan group described the enantioselective reaction of 2-nitrobenzofurans with 3-pyrrolyl-oxindoles in the straightforward construction of chiral 2,3-dihydrobenzofurans (Scheme 1, center). 10 Given the lack of simple additions involving 2-nitrobenzofurans and our continuous research activity in catalytic asymmetric dearomative transformations, 11 we became interested in the development of the enantioselective CADA Michael reaction between electron-deficient 2-nitrobenzofurans 1 and α,β-unsaturated aldehydes 2 . Herein, we report the first organocatalytic dearomative Michael addition realized under NHC catalysis 12 leading to the formation of chiral 2,3-disubstituted-2,3-dihydrobenzo-heterocycles 3 (Scheme 1, bottom).…”
mentioning
confidence: 99%